Effect of diet on molecular relationships between Atlantic cod larval muscle growth dynamics, metabolism, and antioxidant defense system - Vo, Tu A.; Galloway, Trina F.; Arukwe, Augustine; Edvardsen, Rolf B.; Hamre, Kristin; Karlsen, Ørjan; Rønnestad, Ivar; Kjørsvik, Elin (Frontiers in Marine Science, 2022)
We studied molecular effects (RNAseq and qPCR) of first feeding prey types (copepods or rotifers/Artemia) on skeletal muscle myogenesis and growth dynamics (proliferation, differentiation), metabolism (glycolysis, gluconeogenesis, oxidative phosphorylation), and antioxidant defense system (production/regulation of reactive oxygen species (ROS) in cod (Gadus morhua) larval skeletal muscle. Larval somatic growth rates were significantly higher in copepod fed larvae, although shifts in gene expressions related to muscle growth dynamics between hypertrophy and hyperplasia and generation and regulation of ROS mostly occurred around 5-, 10-, and 15-mm standard length (SL) for both groups. Gene expression for cell membrane proteins (such as nox1 and igf1r) peaked at 7 mm SL in all larvae, corresponding with increased ROS expressions in cod muscle during the exponential stratified hyperplasia phase from 7 mm SL. Expression for muscle differentiation (mef2a) occurred continuously (strongest from 10 mm SL). Expressions for muscle proliferation (pcna) and hydrogen peroxide (H2O2) generation (sod1 and sod2) occurred in the 5 - 15 mm SL range, peaking at 10 mm SL in all larvae. A downregulation of sod1 and sod2 in skeletal muscle from 15 mm SL indicated the first response of the defense antioxidant system. Gene expressions related to glucose metabolism (slc2A11, pfk, fpb2, ldha) was 3 - 10 times higher in copepod-fed larvae than in rotifer/Artemia-fed larvae between 7 – 10 mm (live prey period). Copepods move faster than rotifers, and cod larvae will also gradually increase their active swimming periods, due to less viscous forces. Active swimming during the strongest muscle stratified hyperplasia phase (7 – 10 mm SL) could promote a better delivery and transport across the muscle membrane and intracellular flux through glycolysis and oxidative phosphorylation and would contribute to the observed earlier and more effective glucose metabolism in the larvae fed copepods. We suggest that active swimming is an important factor promoting cod larval muscle growth, especially during the strongest muscle hyperplasia phase between 7 and 10 mm SL. The rapid movements of copepods and better nutritional composition could play important roles in stabilizing ROS levels, promoting high swimming activities and enhancing long-term muscle growth in cod.